Response of improved fenugreek (Trigonella foenum-graecum L.) varieties to powdery mildew (Erysiphe polygoni) and it’s performance evaluation under natural field conditions in Wolaita zone, South Ethiopia - Nega, Alemu; Munda, Daniel; Loha, Gobeze (Revista de Ciências Agroveterinárias, 2025)
Powdery mildew is one of the most important diseases that constrain fenugreek production and productivity in fenugreek-growing areas of Ethiopia where mid to high land environmental conditions prevail. Thus, this study was conducted to evaluate the performance and response of six fenugreek varieties to powdery mildew under field conditions in the Wolaita Zone, Southern Ethiopia, in the 2020/2021 cropping seasons. The treatments consisted of six released fenugreek varieties that were laid out in an RCBD with three replications. Disease severity was assessed as the proportion of leaf area affected by the disease on 10 randomly selected plants in the middle two rows. The AUDPC was estimated from the percent severity index. The results revealed that the terminal disease severity varied from 27.00 to 48.67PSI at Sodo Zuria; and 23.67 to 57.33PSI at Damot Gale, respectively. AUDPC varied from 530.80 to 907.07%-days in Sodo Zuria and from 341.80 to 668.50%-days in Damot Gale. The varieties Bishoftu, FG-10, and Challa exhibited high disease severity and high AUDPC and were categorized as susceptible fenugreek varieties. It is concluded that under field conditions, different fenugreek varieties responded differently to powdery mildew, and the disease severity was strongly affected by the use of different resistance levels of fenugreek varieties and differences in the environmental conditions. It is, therefore, promising to use the two varieties, such as Ebbisa and Hunda, which were considered resistant under field conditions and that are recommended to be used by farmers in the study areas and elsewhere with similar agroecologies in Ethiopia.